2012
DOI: 10.1007/s00508-012-0245-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between KCNE1 (G38S) genetic polymorphism and non-valvular atrial fibrillation in an Uygur population

Abstract: The KCNE1 38G is a risk factor for incident AF in an Uygur population. The KCNE1 G38S might have different impact on AF in different ethnicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Characteristics of the studies included for meta-analysis are shown in Table 1. Four [18,23,24,27] of these articles were published in Chinese and 10 [17,1922,25,26,2830] in English. The sample sizes ranged from 130 to 888 of all eligible studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the studies included for meta-analysis are shown in Table 1. Four [18,23,24,27] of these articles were published in Chinese and 10 [17,1922,25,26,2830] in English. The sample sizes ranged from 130 to 888 of all eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 studies, 8 of them [17,19,20,2426,28,29] reported association between KCNE1 G38S polymorphism and risk of AF, whereas the other 6 studies [18,21–23,27,30] reported no significant association. So we conducted the present meta-analysis to evaluate the association between KCNE1 G38S polymorphism and AF.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism by which the KCNE1 112G>A polymorphism contributes to the risk of AF remains poorly understood, a possible explanation may be that the 112G variant is likely associated with an increased I Ks current and high KCNQ1 membrane expression, which may be a genetic determinant of AF (Lai et al, 2002;Zeng et al, 2007;Haijun et al, 2012). KCNE1 is the founding member of the KCNE family of membrane proteins, which are considered to act as selective potassium channel modulators in regulating cellular electrophysiology (Takumi et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple population-based studies have provided evidence of a genetic contribution to AF ( 5 7 ). Mutations in the cardiac ion channel genes were found to play a role in the development of AF ( 8 13 ), but these mutations account for only a small fraction of patients with AF ( 14 , 15 ). Previous genome-wide association studies (GWAS) have indicated several significant candidate genes associated with this complex disorder, including genetic loci PITX2 on chromosome 4q25, ZFHX3 on chromosome 16q22, and KCNN3 on chromosome 1q21 ( 4 ).…”
Section: Introductionmentioning
confidence: 99%